A 20‐year study of suicide death in a statewide autism population. Issue 4 (21st January 2019) - Kirby, Anne V.; Bakian, Amanda V.; Zhang, Yue; Bilder, Deborah A.; Keeshin, Brooks R.; Coon, Hilary
Abstract : Scientific Summary: Growing concern about suicide risk among individuals with autism spectrum disorder (ASD) necessitates population‐based research to determine rates in representative samples and to inform appropriate prevention efforts. This study used existing surveillance data in Utah to determine incidence of suicide among individuals with ASD over a 20‐year period, and to characterize those who died. Between 1998 and 2017, 49 individuals with ASD died by suicide. Suicide cumulative incidence rates did not significantly differ between 1998 and 2012 across the ASD and non‐ASD populations. Between 2013 and 2017, the cumulative incidence of suicide in the ASD population was 0.17%, which was significantly higher than in the non‐ASD population (0.11%; P < 0.05). During this period, this difference was driven by suicide among females with ASD; suicide risk in females with ASD was over three times higher than in females without ASD (relative risk (RR): 3.42; P < 0.01). Among the individuals with ASD who died by suicide, average age at death and manner of death did not differ significantly between males and females. Ages at death by suicide ranged from 14 to 70 years ( M [SD] = 32.41[15.98]). Individuals with ASD were significantly less likely to use firearms as a method of suicide (adjusted odds ratio: 0.33; P < 0.001). Study results expand understanding of suicide risk in ASD and point to the need for additional population‐based research into suicide attempts and ideation, as well as exploration of additional risk factors. Findings also suggest a need for further study of female suicide risk in ASD. Autism Research 2019, 12: 658–666 . © 2019 The Authors. Autism Research published by International Society for Autism Research published by Wiley Periodicals, Inc. Lay Summary: This study examined suicide risk among individuals with autism spectrum disorder (ASD) in Utah over a 20‐year period. Risk of suicide death in individuals with ASD was found to have increased over time and to be greater than in individuals without ASD between 2013 and 2017. Females with ASD were over three times as likely to die from suicide as females without ASD. Young people with ASD were at over twice the risk of suicide than young people without ASD. Individuals with ASD were less likely than others to die from firearm‐related suicides.